Hybrid nanofluids for heat transfer applications – A state-of-the-art review. (October 2018) - Huminic, Gabriela; Huminic, Angel
Highlights: The thermo-physical properties of hybrid nanofluids were investigated. Numerical and experimental studies in various heat exchangers were presented. The correlations for the thermal conductivity, the viscosity, the Nusselt number and the friction factor were analyzed. Abstract: In recent years, a novel class of working fluids which consists from two solid materials dispersed in a conventional fluid was developed and intensely studied. These fluids are called hybrid nanofluids. This paper presents a review of the research recent results concerning the thermo-physical properties (thermal conductivity, viscosity, density and specific heat) and the heat transfer and flow characteristics of hybrid nanofluids used in various heat exchangers. The hybrid nanofluids leads to an increased thermal conductivity and finally to a heat transfer enhancement in heat exchangers. Experimental and numerical results shown in this review indicate that the hybrid nanofluids are working fluids which could improve significantly the heat transfer in heat exchangers, but, there are still needed research concerning to the study of different combinations of hybrid nanoparticles, their mixing ratio, the stability of the hybrid nanofluids, and the understanding the mechanisms which contribution to the heat transfer enhancement.